Comportamento biomecânico de implantes odontológicos de diâmetro estreito - Reis, Taís Alves dos (2019)
Advantages of narrow implants are replacement of small cervical diameter teeth, reduction or avoidance of bone grafts or preliminary orthodontic treatment. Moreover, bone grafts could increase costs, time of treatment and morbidity rate. This doctoral thesis has four specific objectives: 1) Determine survival and failure rates of single narrow diameter implants according to the manufacturers' recommendation, considering all diameters ≤3,5mm, by means of a systematic review. Seven studies had their data extracted. The survival rate found in this systematic review for single narrow diameter implants in low masticatory effort regions was 97%. Twelve failures were described. 2) Evaluate the mechanical behavior of two different Morse taper implant systems. Twenty Morse taper with frictional lock connection with 2.9 mm diameter (FAC), and 20 Morse taper implants, 3.5 mm diameter (CM) were divided into two groups (n=10) and were submitted to strength to failure test, optical microscopic evaluation of fracture, metallographic analysis of the alloy, finite element analysis and strain gauge test. The resistance to fracture was statistically different (p<0.001) between FAC (225.0±19.8 N) and CM (397.3±12.5 N) groups. The optical microscopic evaluation showed that implants fractured in the discontinuity region of the abutment/implant interface, the region of stress accumulation in FEA. Metallographic analysis showed that implants from the FAC group are composed of titanium-aluminum-vanadium alloy. In the strain gauge test, there was no statistical difference (p=0.833) between CM (1064.8±575.04 μS) and FAC (1002.2±657.6 μS). 3) Investigate the mechanical behavior through fatigue limit test of the 2.9mm diameter implant. Besides, it was investigated the Morse effect of two different Morse taper systems: 2.9mm diameter (FAC group) and 3.75mm diameter (CM group) through pull-out test. The null hypothesis was that the tensile strength of the components for the two groups were similar. Thirteen specimens underwent the fatigue limit test. Only five did not fail with the frequency and number of cycles determined. Three of them did not fail with a load of 130N. In the pull-out test there was a significant difference between the FAC and CM groups (P<0.001). According to fatigue test, the Facility implant was compatible with low masticatory effort regions, as indicated by manufacturer. The best performance of the FAC group in the pull-out test may be due to its internal conical portion with 5o of angulation and its Morse connection. 4) Describe a clinical case of agenesis of a lower lateral incisor, whose indication was the installation of a narrow implant and subsequent rehabilitation. The indication of narrow implants must be made with caution, since they have very specific biomechanical characteristics, inferior to the implants of regular diameter. Some features of the Facility implant may have favored its mechanical performance within the acceptable clinical standards for its indications.